Kontribusi Ekonomi Usaha Kerajinan Tikar Mendong (Fimbristylis Globulosa) Terhadap Pendapatan Rumah Tangga Petani di Kecamatan Lenek Kabupaten Lombok Timur - Tina Nopiana; Candra Ayu; Ibrahim Ibrahim (JURNAL AGRIMANSION, 2022)
ABSTRACT This study aims to: (1) analyze the types of productive economic activities of respondent farmer households in Lenek District East Lombok Regency; (2) analyzing the income from the mendong mat crafts business and its contribution to farmer households income in Lenek District of East Lombok Regency; (3) Knowing the problems and obstacles faced by the craftsmen in managing the mendong mat craft business in Lenek District East Lombok Regency. This research uses descriptive method. Analysis of the data used is the analysis of income and business contributions. The results of the study showed that: (1) There were 7 types of productive economic activities carried out by respondents farmer household in Lenek District including; mendong mat craft business, farming, farm laborers, tobacco processing workers, construction workers, shop employees and migrant workers. (2) The income from the mendong mat craft business is Rp 6,115,239,83/year with a contribution of 30.40% to the total household income in farm in Lenek District. The contribution of the mendong mat craft business gave a significant contribution to increasing the household income of the respondent farmers. (3) The problems and obstacles of craftsmen in managing the mendong mat craft are the low quality of mendong dyes, low product development skills, traditional weaving equipment, low ability to market the product of the type of a Alus mat, the price of the product mat is still low, high prices of raw materials, and its own capital for business development. Keywords: productive economy, mendong mat crafts, income, contribution